Prognostic implication of a ferroptosis-related gene signature associates with immunity in Ewing’s sarcoma - Jiao, Xiejia; Li, Qingbo; Xu, Xiao (Electronic Journal of Biotechnology, 2023)
[Display omitted] Ewing's sarcoma is an extremely aggressive bone sarcoma in teenagers and adolescents. We managed to identify the potential role of ferroptosis-related genes (FRGs) in Ewing's sarcoma and its clinical prognostic value. A total of 59 common differentially expressed FRGs were screened out. GO/KEGG enrichment and PPI network were executed. Based on 16 prognostic-related FRGs identified by univariate Cox regression in GSE17674, 2 molecular clusters were screened out via NMF consensus. Survival rate and immune infiltration were totally different in two clusters. Subsequently, multivariate/step Cox regression was conducted to identify 7 risk signatures (SLC2A1, PCK2, CHAC1, ATG13, PRKAA2, ARNT, and SIRT1). K-M survival (p = 1.785e-06) and ROC curves (with AUC value 0.816, 0877, 0.919 in 1, 3, 5 years) were plotted to assess the good predictive ability of risk model. ICGC dataset with K-M survival (p = 1.558e-02) and AUC value (0.886, 0.750, 0.709 in 1, 3, 5 years) was used to validate the risk model. Risk score and clinical features (gender, age stage status) were incorporated into a nomogram model. Immune microenvironment (IME) ingredients (ESTIMATE score, immune cells, immune-related pathways, and checkpoint genes) between two risk groups were also explored. High-risk group possessed an activated immune status compared to low-risk group. Finally, prognostic signatures exhibited perfect diagnostic ability in ES occurrence, and several drugs showed IC50 sensitivity to different risk groups. Our study identified 7 prognostic signatures of FRGs and explored related immune infiltration which provided new aspects for future research in Ewing's sarcoma. How to cite: Jiao X, Li Q, Xu X. Prognostic implication of a ferroptosis related gene signature associates with immunity in Ewing’s sarcoma. Electron J Biotechnol 2023;64. https://doi.org/10.1016/j.ejbt.2023.01.004.